Immobilization of 129I in nuclear waste glass matrixes synthesized under high-pressure conditions: an experimental study. Issue 42 (20th October 2021) - Morizet, Yann; Hamon, Jonathan; La, Carole; Jolivet, Valentin; Suzuki-Muresan, Tomo; Paris, Michael
Abstract : Two recommendations are suggested for immobilizing 129 I radioisotopes in high-pressure glasses: the use of an oxidized iodine form (I 5+ ) instead of the reduced iodine form (I − ) and the use of a sodium rich composition instead of a calcium rich one. Abstract : There is major environmental interest in finding a sustainable solution to immobilize 129 I, a by-product of the nuclear industry. The use of aluminoborosilicate glasses represents a good compromise. However, this solution does not appear adequate for 129 I owing to its volatility at high temperature during the vitrification process. In the present work, we use a high-pressure (1.5 GPa) apparatus to synthesize I-rich aluminoborosilicate glasses. We show that the use of high-pressure conditions enhances the I solubility in glasses by several orders of magnitude as compared to 1 bar synthesis, with I solubility up to 5.7 mol%. We observed that I is more solubilized in Na-rich as compared to Ca-rich glass. Investigation of the I speciation using XPS also reveals that I solubility in glasses is much higher as I dissolves as I 5+ in comparison to I − . Our work shows that using high-pressure appears to be a reliable solution for dissolving a large quantity of I within the structure of aluminoborosilicate glasses for the conditioning of nuclear waste. We also demonstrate that the oxidized I waste form should be employed to greatly increase I solubility in nuclear waste glasses. Therefore, it represents a potential pathway for solving the immobilization of 129 I produced by anthropic nuclear activity.